Health surveillance of preschool children. Issue 6541 (26th July 1986) - Colver, A F; Steiner, H
Abstract : Discussions with every general practice, health visitor, and clinical medical officer in Northumberland Health Authority led to agreement about the content of preschool health surveillance, the ages at which it should be done, and referral pathways after a failed screening test. Each primary health care team now undertakes to do a basic minimum set of screening tests, and each team decides who in the team will do each test. The screening system agreed on should enable time to become available for the equally important aspects of surveillance--namely, developmental guidance, health education, and assessment and follow up of problems. The discussions also led to agreement about how the health authority should evaluate the effect of the surveillance programme on the health of children.